Effect of biofertilizers on floral attributes and corm yield of gladiolus (Gladiolus grandiflorus) under hilly condition of Uttarakhand, India (Current Horticulture, 2024)
An experiment was conducted to study the effect of biofertilizers on floral attributes and corm yield of gladiolus (Gladiolus grandiflora L.) var. Arka Amar at Floriculture and Landscaping Block, College of Horticulture, VCSG, Uttarakhand University of Horticulture and Forestry, during 2016. The experiment consists of eight treatments, viz. control, PSB @ 2ml/l, Azotobacter @ 25g/l, VAM @ 20g/l and their combinations. Recommended doses of fertilizer were applied as a common basal dose in all treatments. The experiment was laid out in randomized complete block design and replicated thrice. The results revealed that minimum number of days were taken to first floret opening (111.76) and maximum number of spike per plant and per plot (2.00 and 32.00, respectively), floret diameter (12.46 cm) and number of corms per plot (31.00) were recorded from the corms inoculated with PSB @ 2ml/l + Azotobacter @ 25 g/l + VAM @ 20 g/l. There was maximum corm weight (60.60 g), corm diameter (6.20 cm), numbers of cormels per plant and per plot (37.33 and 600.76, respectively) from the corms inoculated with Azotobacter @25 g/l +VAM @20 g/l, followed by PSB @ 2ml/l + Azotobacter @ 25 g/l + VAM @ 20 g/l. Thus, it can be concluded that application of PSB @ 2ml/l + Azotobacter @ 25 g/l + VAM @ 20 g/l can be used for getting superior quality and yield in gladiolus var. Arka Amar.
Keywords: Azotobacter; Corms; Cormels; VAM; PSB; Recommended doses of fertilizers